2011
DOI: 10.1080/10538712.2011.541010
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Sexually Victimized and Nonsexually Victimized Male Adolescent Sexual Abusers: Developmental Antecedents and Behavioral Comparisons

Abstract: This study compares sexually victimized and nonsexually victimized male adolescent sexual abusers on a number of variables. Self-report measures were administered to 325 male sexually abusive youth (average age 16) in six residential facilities in the Midwest, 55% of whom reported sexual victimization. The results indicate that the sexually victimized sexual abusers have more severe developmental antecedents (trauma, family characteristics, early exposure to pornography and personality) and recent behavioral d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 30 publications
4
47
0
3
Order By: Relevance
“…The pathways to juvenile sexual offending are certainly varied and complex (Burton, Duty, & Leibowitz, 2011). The etiology of sexually abusive behaviors seems to be fostered by early attachment disruptions, whereby attempts are made to satisfy unmet emotional and intimacy needs through sexual or aggressive means (Bushman, Baumeister, & Phillips, 2001;Grady, Levenson, & Bolder, 2016;Marshall, 2010;Smallbone & Dadds, 1998).…”
Section: The Link Between Early Adversity and Development Of Sexual Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathways to juvenile sexual offending are certainly varied and complex (Burton, Duty, & Leibowitz, 2011). The etiology of sexually abusive behaviors seems to be fostered by early attachment disruptions, whereby attempts are made to satisfy unmet emotional and intimacy needs through sexual or aggressive means (Bushman, Baumeister, & Phillips, 2001;Grady, Levenson, & Bolder, 2016;Marshall, 2010;Smallbone & Dadds, 1998).…”
Section: The Link Between Early Adversity and Development Of Sexual Bmentioning
confidence: 99%
“…Engaging youths in activities that foster self-efficacy is profoundly important, as they can promote cognitive transformation by which maltreated youths begin to view themselves as competent and worthy of love and respect. Treatment for juveniles who have committed sexual offenses has historically relied heavily on psycho-educational models focused on distorted thinking about sexual abuse and relapse prevention, but should emphasize process-oriented relational interventions that can help youths improve interpersonal skills and alter general maladaptive cognitive schema (Burton et al, 2011;Cicchetti & Banny, 2014).…”
Section: Implications For Trauma-informed Social Work Practice and Pomentioning
confidence: 99%
“…5.6% (N:5) and 8.9% (N:8) of the incidences were related to dangerous and severe injuries, respectively. As "severe" where identified injuries that threat children's life, or a weapon with potential to cause serious injury, such as a knife, gun or bat had been used [10][11][12]. It is important to mention, that the majority of severe injuries resulted in the death of the victim (62.5% and N:5), and the children who survived manifest heavy residual damage (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…A report from the National Society for the Prevention of Cruelty to Children (NSPCC) in the United Kingdom on child maltreatment, found that 12% of children under 11years old and 17.5% of children between 11-17years had been exposed to domestic violence between adults in their homes during childhood [11]. Furthermore, domestic violence is a factor that is strongly associated with the group of young people who begin offending at an early age and who continue offending as adults [12]. It is therefore essential to take into consideration domestic violence when exploring child maltreatment.…”
Section: Discussionmentioning
confidence: 99%
“…VanWijk, Maliand et Bullens (2007) proposent quant à eux de classifier les AAAS sur la base de l'âge à la première infraction. D'autres auteurs ont suggéré une typologie basée sur la présence ou non de maltraitance vécue durant l'enfance (Burton, Duty et Leibowitz, 2011). Le lien entre le fait d'avoir été victime et auteur d'une agression sexuelle a fait l'objet de plusieurs études.…”
Section: Introductionunclassified